Nonmonotonous evolution of the Kondo temperature in the phase diagram of Ce(Pd1-xCux)(2)Si-2 - Berisso, M.G.; Trovarelli, O.; Pedrazzini, P.; Zwicknagl, G.; Geibel, C.; Steglich, F.; Sereni, J.G.; Sereni, Julián; Pedrazzini, Pablo (American Physical Society, 1998)
Fil: Gómez Berisso, M. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina